2022
DOI: 10.2196/32400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an AIDS Educational Mobile Game (AIDS Fighter · Health Defense) for Young Students to Improve AIDS-Related Knowledge, Stigma, and Attitude Linked to High-Risk Behaviors in China: Randomized Controlled Trial

Abstract: Background The AIDS epidemic among young students is serious, and effective preventive interventions are urgently needed. Game-based intervention has become an innovative way to change healthy behaviors, and we have developed an AIDS educational game called AIDS Fighter · Health Defense. Objective In this study, we tested the effect of AIDS Fighter · Health Defense on young students in improving AIDS-related knowledge, stigma, and attitude related to hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…According to statistics found in this study, among newly infected HIV patients in Chongqing recorded every year, the proportion of MSM showed an increased trend. However, this proportion in Chongqing was higher than the national average [9,10]. Therefore, it is of great social and practical significance to prevent and treat diseases among MSM in Chongqing.…”
Section: Discussionmentioning
confidence: 96%
“…According to statistics found in this study, among newly infected HIV patients in Chongqing recorded every year, the proportion of MSM showed an increased trend. However, this proportion in Chongqing was higher than the national average [9,10]. Therefore, it is of great social and practical significance to prevent and treat diseases among MSM in Chongqing.…”
Section: Discussionmentioning
confidence: 96%
“…In our previous studies, an AIDS educational game called AIDS Fighter· Health Defense was developed, and a randomized controlled trial was conducted and proved that this game has a good education effect on AIDS prevention for young students. Students have good comments on the game and believe it could help them learn more about AIDS [ 36 ]. In this study, we would like to evaluate the effect of this game to improve ART adherence of young people newly diagnosed with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Players are required to collect ART medicine and condoms, avoid HIV, alcohol and drug, take ART medicine regularly, and answer questions about ART. More information about the game can be found in our published studies [ 35 , 36 ]. It had been shown that the game can improve the AIDS-related knowledge and has the potential to improve AIDS prevention ability of young students.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few effect evaluations of HIV/AIDS educational games in China found that the hero combat game AIDS Fighter • Health Defense did not have a significant effect on decreasing HIV-related stigma [40]. The researchers suggested that the decrease in stigma may need time to take effect.…”
Section: Comparison With Prior Workmentioning
confidence: 99%